2021
DOI: 10.1098/rsos.211172
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Rhodococcus erythropolis SY095 modified with functional magnetic Fe 3 O 4 nanoparticles

Abstract: Alkali-surfactant-polymer flooding technology is widely employed to extract crude oil to enhance its production. The bacterial strain Rhodococcus erythropolis SY095 has shown high degradation activity of alkane of crude oil. In the past, many treatment strategies have been implemented to reduce oil concentration in wastewater. Previous studies mainly focused on the extracellular products of Erythrococcus rather than its degradation properties. In the current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The results indicated that the MF enhanced the adhesion tendency. In the enhancement of the positive charge on the surface of the MMPP caused by the changes of the mixed liquor colloid under the MF, the MMPP became more attractive to the microbes with negative cytomembrane than the MPP and the PP (Ma et al 2021 ). Subsequently, sequential batch degradation of the MMPP and MPP was operated, and increasing trends of Cl − as well as attached and suspended biomass accumulation were observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the MF enhanced the adhesion tendency. In the enhancement of the positive charge on the surface of the MMPP caused by the changes of the mixed liquor colloid under the MF, the MMPP became more attractive to the microbes with negative cytomembrane than the MPP and the PP (Ma et al 2021 ). Subsequently, sequential batch degradation of the MMPP and MPP was operated, and increasing trends of Cl − as well as attached and suspended biomass accumulation were observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The representatives of the genus Rodococcus have been the focus of numerous research investigations and reviews related to the genus's capacity to catabolize a variety of difficultto-degrade, environmentally hazardous compounds. These bacteria often find real use in biotechnological processes linked to the purification of industrially polluted waters and soils [8,11,39].…”
Section: Discussionmentioning
confidence: 99%